Long-term impact of the 2011 Great East Japan Earthquake and tsunami on functional disability among older people: A 3-year longitudinal comparison of disability prevalence among Japanese municipalities. (December 2015) - Tomata, Yasutake; Suzuki, Yoshinori; Kawado, Miyuki; Yamada, Hiroya; Murakami, Yoshitaka; Mieno, Makiko Naka; Shibata, Yosuke; Ojima, Toshiyuki; Hashimoto, Shuji; Tsuji, Ichiro
Abstract: It has been unclear whether the prevalence of disability is higher in an area affected by natural disaster than in other areas even if more than one year has passed since the disaster. The aim of this ecological study was to examine whether the rate of increase in disability prevalence among the older population was higher in disaster-stricken areas during the 3 years after the Great East Japan Earthquake (GEJE) and tsunami. This analysis used public Long-term Care Insurance (LTCI) data covering 1570 municipalities. "Disaster areas" were considered to be the three prefectures most affected by the earthquake and tsunami: Iwate, Miyagi, and Fukushima. The outcome measure was the number of aged people (≥65 years) with LTCI disability certification. Rates of change in disability prevalence from January 2011 to January 2014 were used as the primary outcome variable, and compared by analysis of covariance between "coastal disaster areas", "inland disaster areas" and "non-disaster areas". The mean rate of increase in disability prevalence in coastal (14.7%) and inland (10.0%) disaster areas was higher than in non-disaster areas (6.2%) ( P  < 0.001). During the 3 years after the earthquake, the increase of disability prevalence from before the GEJE continued to be higher in the disaster-stricken areas. Highlights: This study examined the three-year impact of this earthquake on disability in older people. Disability prevalence continued to increase in disaster-stricken areas. Earthquake may chronically increase the risk of disability in disaster-stricken areas. This is the first study of this disaster to have employed data from all municipalities in Japan.